ChemInform Abstract: Pd(II)‐Catalyzed Enantioselective Synthesis of P‐Stereogenic Phosphinamides via Desymmetric C—H Arylation. Issue 26 (June 2015) - Du, Zhi‐Jun; Guan, Jing; Wu, Guo‐Jie; Xu, Peng; Gao, Lian‐Xun; Han, Fu‐She
Abstract Optimized conditions are elaborated which include a protected tyrosine as the optimized optically active ligand.